The handbook of language teaching - Long, Michael H.; Doughty, Catherine J. (Chichester, U.K : Malden, MA : Wiley-Blackwell, 2011)
Bringing together an international team of specialists from the fields of applied linguistics, second language acquisition, linguistics, education, and psychology, The Handbook of Language Teaching is a wide-ranging and invaluable reference guide.
Includes index.
Keywords: Language and languages -- Handbooks, manuals, etc. -- Study and teaching; Second language acquisition -- Handbooks, manuals, etc; 17.41 language teaching